Emotional health and well-being : a practical guide for schools - Cowie, Helen (Paul Chapman Pub. ; SAGE Pub., 2004)
P̀rofessor Cowie and her colleagues have produced a valuable tool for use in all schools on both micro and macro level' - Education Review. T̀he book is an impressive and useful handbook of advice and resources. More than that, because it presents so much evidence, it's able to show, rather than tell, how schools can improve life for their pupils and teachers' - Gerald Haigh, Times Educational Supplement, Friday Magazine. This book describes behaviours, both disruptive and secretive, which indicate emotional distress, and presents a range of tried and tested strategies.